E-government Program Implementation in Public Elementary Schools in Sorsogon, Philippines - Daradar, Maribel Bartolay; Pinca-Atutubo, Virginia (Jurnal Pendidikan Progresif, 2023)
E-government Program Implementation in Public Elementary Schools in Sorsogon. Objectives: This study determined the e-government programs, extent, and challenges in Public Elementary Schools in Sorsogon, Philippines. Methods: This study utilized the mixed-methods sequential-explanatory design in which the major design is quantitative and minor is qualitative research where one thousand  elementary teachers and sixty-eight elementary school heads at Sorsogon West Ditrict, Sorsogon City, Philippines were selected using stratified random (percentage) sampling. Data was collected through document analysis, survey questionnaire, and unstructured interviews. Findings: The results revealed that first, there were various e-government programs implemented across the identified variables in the study, second; the e-government programs are well-implemented; third, the school heads and teachers experienced challenges in the implementation of the programs; and fourth, a strategic plan will help strengthen and enhance the e-government programs implementation. Conclusion: Determining the extent of implementation of e-government programs and factors affecting its implementation provides basis to further develop and strategically improve its implementation. Keywords: e-government, e-government program implementation, e-government extent of implementation, strategic plan.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202340